Facile synthesis of Ni3Se4/Ni0.6Zn0.4O/ZnO nanoparticle as high-performance electrode materials for electrochemical energy storage device. (20th February 2023) - Runfa, Li; Chen, Xin; Hongliang, Cao; Wei, Yan; Yuanfang, Zhang; Siyu, Cheng; Wenrui, Jiang; Qi, Zhang; Yi, E; Meng, Jiang; Abdullah, Muhammad; Tan, Liyi
Abstract: To enhance the performance of transition metal chalcogenide composite electrode material, a key point is a composite design and preparation based on the synergistic effect between the oxide and selenide materials. With a facile 'one step template-annealing' step, Ni3 Se4, Ni0.6 Zn0.4 O and ZnO are simultaneously synthesized, by 500 °C annealing. With the increase of annealing temperature from 350 °C to 600 °C, nickel selenides change from NiSe2 to Ni3 Se4 to NiSe. The charge storage capacity increases first and then decreases with the increase of annealing temperature, and the 500 °C annealing obtained three compound composite Ni3 Se4 /Ni0.6 Zn0.4 O/ZnO (NNZ-500) nanoparticle material displayed a high specific capacitance of 1089.2 F g −1 at 1 A g −1, and excellent cycle stability of 99.8% capacitance retention after 2000 cycles at 5 A g −1 . Moreover, an asymmetric supercapacitor was assembled with NNZ-500 as the positive electrode material and activated carbon as the negative electrode material. This kind of asymmetric supercapacitor demonstrated a high energy density of 53.4 Wh kg −1 at 819.0 W kg −1, and cycle stability with 98.6% capacitance retention after 2000 cycles. This material preparation approach provides great potential for the future development of high performance transition metal composite electrode materials in energy storage applications.